PECULIARITIES OF TRAINING FOR CAREER OF LEARNERS WITH MILD INTELLECTUAL DISABILITIES - Virbalienė, Rita; Baranauskienė, Ingrida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This article describes the peculiarities of training of learners with mild intellectual disabilities. The aim of the article is to highlight problems and different theoretical approaches and theoretically validate the optimal ways of training for career of learners with mild intellectual disabilities. On the basis of scholarly literature, to analyses which areas of training for career are accessible to learners with mild intellectual disabilities. To discuss training for career as a person’s readiness to enter adult life from the point of view of education. Young people with mild intellectual disabilities should be supported in understanding own wishes and possibilities. It is important that they start preparing for professional activity in early childhood, since it continues until a person becomes an adult. In the childhood, children should be introduced with different professions and encouraged to take interest in them. They should be encouraged to think about their future work, what they are successful at, as well as about the advantages of different activities.